Approximation to a landlord port management model: Ukrainian context - Volodymyr Shemayev (Розвиток методів управління та господарювання на транспорті, 2020)
With the beginning of port reform in Ukraine, the model of port sector governance was changed. Established in 2013, the Ukrainian Sea Ports Authority was endowed with administrative, maritime safety and security functions. Purely commercial activities remained with public and private stevedoring companies and marine terminals. This distribution of functionality in seaports has brought the domestic governance model closer to the well-known in North America and North-Western Europe – landlord-port model. The aspects identified as a result of the study, namely control over land plots, legal status of the Ukrainian Sa Ports Authority, the presence of state stevedores, and unsettled relations with local authorities, do not allow to classify the domestic port governance model in the classical sense of landlord-port. The latter points rather to a hybrid model in Ukraine with some elements of landlord-port model, such as concessions, private participation in services etc. The most vulnerable element in the context of the port-landlord model at the Ukrainian Sea Ports Authority is the lack of a mechanism for managing port areas due to the presence of several types of landowners in a seaport including public, local and private entities. The article proposes a number of measures, including corporatization of the Ukrainian Sea Ports Authority, amendments to the legislation, innovations in the distribution of concession fees, support of the state's exit from the stevedoring activity segment in ports, as well as an inventory of port territories, the implementation of which can qualitatively bring the Ukrainian model closer to the port management practices of North-Western Europe. In addition, involvement of local authorities into activities of seaport councils as permanent members, and -after corporatization of Ukrainian Sea Ports Authority- to participate in pilot projects of joint ownership of autonomous port authorities (for example in the ports of Odessa and Mykolayiv) could facilitate a sustainable cooperation between a port and local governance.